(3CNHGQ GdbVGIs - (3CHh HcQ eMeO Hf Nda Hf MjGf Hf UObI, GHf hcjY,J (B306 (3g` s
(3ChdgG (B:s
(3GeG HYO aEf Gddg YR hLd HGbGeJg GdMb Hjf YHGOg LYd GdMce Hjfge GQaY GdGTjGA hGLdgG NWQkG hGSJNda GdNdaGA ai GdCQV s
(3BNQgG (B:s
(3aSCd GdeOYi Yjfg aGMdag adeG bGd dg bd hGddg GHJG abGd hGddg Ke bGd hGRjOc CjgG GdbGVi GdWGdH GdZGdH aNQ ejJkG hMed s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B114s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B225 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2/ 1 - (3U (B8 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs